Effects of maltodextrin content in double-layer emulsion for production and storage of spray-dried carotenoid-rich microcapsules - Ribeiro, Mírian Luisa Faria Freitas [UNESP]; Roos, Yrjö Henrik; Ribeiro, Ana Paula Badan; Nicoletti, Vânia Regina [UNESP] (Elsevier, 2020)
This work aimed to produce carotenoid-rich microcapsules by spray drying of buriti oil emulsions stabilized by soy protein isolate and high-methoxyl pectin, added with maltodextrin. Microcapsules were produced by spray drying of emulsions containing 28 g buriti oil/100 g and 1.8 g wall material/100 g added with maltodextrin at different contents: 0.75, 1.00, and 1.25 g maltodextrin/g total solids in the emulsion. The microcapsules were analyzed for color, moisture content, encapsulation yield, particle size distribution, encapsulation efficiency and retention of carotenoids, encapsulation efficiency and retention of oil, water sorption, water plasticization, mechanical relaxation, and morphology by optical and scanning electron microscopy. The highest maltodextrin content resulted in higher yield, encapsulation efficiency, and carotenoid retention. Moisture content was around 0.70% w/w (d.b.) and particle size distribution was unimodal, with mean diameter around 30 μm. The glass transition and relaxation temperatures of the microcapsules were dependent on relative humidity and mechanical relaxation occurred at least 30 °C above the glass transition temperature. The microcapsules were poly-nucleated, spherical, with few wrinkles, no apparent cracks, and presence of some aggregates. The results showed that the produced buriti oil microcapsules are suitable for application in carotenoid enrichment of foods, as well as a natural dye.
Keywords: Carotenoid-rich microcapsules; Emulsion spray drying; Glass transition temperature; Protein/pectin complex; Relaxation temperature; Scanning electron microscopy